2017
DOI: 10.1007/978-3-319-56091-5_7
|View full text |Cite
|
Sign up to set email alerts
|

Urban Wetlands and Riparian Forests as a Nature-Based Solution for Climate Change Adaptation in Cities and Their Surroundings

Abstract: Wetlands and riparian forests belong to the most productive, but also the most vulnerable, ecosystems in urban regions and cities due to their complex watershed system, often very high biodiversity and the pressure from urban land use and surface sealing. Wetlands and floodplain forests are often highly valued recreational areas, providing many benefits for urban dwellers, such as fresh air, moisture, oxygen and biogenic essentials as well as many cultural and place-based values. Wetlands and riparian forests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
1
24
0
2
Order By: Relevance
“…As stated by variety of stakeholders, the long-term benefits are not clearly defined for them and for citizens, which pose an additional task for the city to visualize the effects of projects regarding the long-term benefits [7,9,11,13,17,19,37]. As our previous research shows, very few trade-offs were identified so far, such as eco-gentrification, ecosystem disservices, etc.…”
Section: Limitatations Associated With Trade-offs and Conflicts Arounmentioning
confidence: 97%
See 4 more Smart Citations
“…As stated by variety of stakeholders, the long-term benefits are not clearly defined for them and for citizens, which pose an additional task for the city to visualize the effects of projects regarding the long-term benefits [7,9,11,13,17,19,37]. As our previous research shows, very few trade-offs were identified so far, such as eco-gentrification, ecosystem disservices, etc.…”
Section: Limitatations Associated With Trade-offs and Conflicts Arounmentioning
confidence: 97%
“…The second group of challenges includes those caused by environmental risks connected to climate change-i.e., flooding and heat waves. The last big floods in Germany (stemming from the Elbe, Oder, Mulde, and Rhine) drew attention to the fact that technical or manufactured water protection is not 100% effective, particularly when taking climate change and longer heavy precipitation events into consideration [16,17]. Moreover, with its hazardous bursting of large dams, the last Elbe flood in Germany in 2013 made it very clear that the failure of technological solutions can result in enormous damage and casualties.…”
mentioning
confidence: 99%
See 3 more Smart Citations